Professional academic development - the influence of context on motivation - Leibowitz, B.L. (South African Journal of Higher Education, 2016)
This study explores the relationship between intrinsic motivation, extrinsic motivation and contextual social and material conditions influencing the desire of academics to learn to teach at three South African universities. It considers these three influences from the perspective of self-determination theory, and argues that the theory is relevant for a discussion on motivation to learn to teach, but that the theory should be modified to take into account a more socio-political perspective. A careful analysis of these forms of intrinsic and extrinsic motivation in combination with contextual influences has implications for national and institutional policy on professional academic development. The study suggests that extrinsic forms of motivation may play an important role in encouraging academics to participate in professional development opportunities, but they are rendered less effective by sub-optimal social and material conditions, and thus by issues of social injustice and inequality. The study is based on interviews with 31 academics at three South African universities.